Colorectal cancer: a health and economic problem - Klimeck, Leon; Heisser, Thomas; Hoffmeister, Michael; Brenner, Hermann (Best practice & research. Clinical gastroenterology, 2023)
Colorectal Cancer (CRC) is the third most commonly diagnosed form of cancer and accounts for approximately 1.9 million cancer cases each year (10% of all new cancer cases globally). Incidence strongly increases with age and has been traditionally highest in Western, affluent countries, but it is rapidly increasing in many less developed countries and in younger generations in both developed and developing countries. With demographic aging, CRC will pose a rapidly increasing challenge for many societies, which underlines the need for major efforts on primary and secondary prevention. A number of effective screening options are available, and implementation of well-organized screening programs could have a major impact on lowering the future burden of the disease.